Effect of Systemic Inflammation on the Function of Insulin and Glucose Metabolism in Rheumatoid Arthritis - Sebastian Herlitz-Cifuentes, Herbert; Carola Fernandez Garces, Paulina; Ivone Lamperti Fernandez, Liliana; Alberto Guzman-Gutierrez, Enrique (Current Diabetes Reviews, 2016)
Rheumatoid arthritis (RA) is a systemic autoimmune disease of unknown etiology characterized by chronic inflammation of the synovial membranes and articular structures of the joints. The concomitant comorbidities are important in the management and treatment of patients with RA, because they decrease their life quality and expectancy – with cardiovascular diseases being the most common comorbidities and primary cause of death in RA. Traditional cardiovascular risk factors, such as diabetes mellitus (DM) and insulin resistance (IR) are prevalent in these patients. The prevalence of DM in RA patients has not been well established and the association between these diseases is controversial. On the other hand, several epidemiological studies support the association between RA and IR, with the latter being linked to systemic inflammatory markers, including C reactive protein and erythrocyte sedimentation rate. Patients with RA who underwent glucocorticoid therapy were also determined to have a defective insulin sensitivity and pancreatic β-cell dysfunction. It has been proposed that systemic inflammation due to RA may result in insulin resistance – moreover, studies have examined the effect of inflammatory cytokines such as TNF-α, IL-6 and IL-1 on insulin sensitivity and glucose metabolism. Likewise, the association between RA and IR, and its role on the different characteristics of the disease, such as duration, activity, and treatment with glucocorticoids has not been well defined. A gap in the current understanding regarding the role that the systemic inflammation and the different RA characteristics have on the insulin function and glucose metabolism of RA patients suggest that more studies are required to elucidate these mechanisms.
Keywords: insulin resistance